2020
DOI: 10.1093/cercor/bhaa331
|View full text |Cite
|
Sign up to set email alerts
|

3D Synaptic Organization of the Rat CA1 and Alterations Induced by Cocaine Self-Administration

Abstract: The hippocampus plays a key role in contextual conditioning and has been proposed as an important component of the cocaine addiction brain circuit. To gain knowledge about cocaine-induced alterations in this circuit, we used focused ion beam milling/scanning electron microscopy to reveal and quantify the three-dimensional synaptic organization of the neuropil of the stratum radiatum of the rat CA1, under normal circumstances and after cocaine-self administration (SA). Most synapses are asymmetric (excitatory),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 129 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…The proportion of AS to SS in the present study (97.1/2.9) is also similar to the previously calculated proportion (97.5/2.5) (Santuy et al, 2020), or the reported 3% of inhibitory synapses in thin dendrites, which predominate in our sample (Megías et al, 2001). The density of synapses in the rat SR is about 2.2 to 2.5 synapses/µm 3 (Blazquez-Llorca et al, 2021; Mishchenko et al, 2010; Sorra et al, 1998). In L1 and L3, we found synaptic densities of 1.80 and 1.08 synapses /µm 3 , respectively, that is, clearly lower than in the SR.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of AS to SS in the present study (97.1/2.9) is also similar to the previously calculated proportion (97.5/2.5) (Santuy et al, 2020), or the reported 3% of inhibitory synapses in thin dendrites, which predominate in our sample (Megías et al, 2001). The density of synapses in the rat SR is about 2.2 to 2.5 synapses/µm 3 (Blazquez-Llorca et al, 2021; Mishchenko et al, 2010; Sorra et al, 1998). In L1 and L3, we found synaptic densities of 1.80 and 1.08 synapses /µm 3 , respectively, that is, clearly lower than in the SR.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of AS to SS in the present study (97.1/2.9) is also similar to the previously calculated proportion (97.5/2.5) 48 , or the reported 3% of inhibitory synapses in thin dendrites, which predominate in our sample 49 . The density of synapses in the rat SR is about 2.2–2.5 synapses/µm 3 50 52 . In L1 and L3, we found synaptic densities of 1.80 and 1.08 synapses/µm 3 , respectively, that is, clearly lower than in the SR.…”
Section: Discussionmentioning
confidence: 98%
“…Almost all (91-99%) spinous synapses in the CA1 and cortex of rodents and primates are excitatory. 66 , 71 , 72 , 73 , 74 , 75 , 76 In adult rat CA1, 100% of perforated and 64% of nonperforated synapses contain AMPA receptors, and 100% of both subtypes contain NMDA receptors. 67 , 77 Similarly, atypically large nonperforated synapses in adult rat CA1 contain more AMPA and NMDA receptors than typical nonperforated spinous synapses (Nicholson & Geinisman 2009).…”
Section: Discussionmentioning
confidence: 99%